A noção do sintoma histérico na constituição da causalidade psíquica da primeira tópica freudiana. - Boufleur, Sandra Cristina (2020)
The aim of this study is to seek the importance of the notion of hysterical symptom for the construction of a psychic causality in the Freudian first topography, and to understand the relevance that it occupies for the development of Freud’s metapsychology. We started this work from the theoretical environment in which Freud was inserted. The context in which he developed his empirical research had a strong anatomopathological and physicalist perspective. Therefore, although his initial ideas about the hysterical symptom took into account psychological explanations for their formation, for example, the psychic trauma, they were strongly linked to organic assumptions. However, in The Interpretation of Dreams (1900), Freud, when investigating memories through regression, introduces an eminently psychic causality for the formation of the hysterical symptom, which will give rise to the formation of the psychic apparatus, divided into unconscious, preconscious and conscious (first topography). The concept of impulse was fundamental so that we could advance in understanding this psychic causality of the hysterical symptom and establish your bond with the body. We sought to show, through the adopted methodology, that the “movement of Freudian thought” understands the hysterical symptom not just as a possibility to expose a properly psychic causality but also as a constituent structure of the subject itself, beyond a mere pathology. In order for this path to be possible, we used works covering the period between 1888 and 1911, such as Hysteria (1888), The Interpretation of Dreams, Three Essays on the Sexual Theory (1905) and Formulations on the Two Principles of Mental Functioning (1911).